Development of cartographic styling tool to support geospatial data interoperability - Rashidan, Muhammad Hanis (2018)
Cartographic styling is a technique used to present geographic data layers in various ways, and controls the appearance of geospatial data. Current practices used to maintain and store cartographic styling are through stylesheet formats, such as Styled Layer Descriptor, Esri layer file, and QGIS Style. However, the use of these formats in current geospatial applications is limited, especially in cross-platform applications. Therefore, a geospatial data format called GeoPackage has been used in this study to provide a new technique of maintaining cartographic styling, apart from the current practices. GeoPackage is an emerging geospatial data format introduced by Open Geospatial Consortium (OGC), with features including open-standard, independent, portable, robust, and cross-platform applications. In this study, a styling extension for GeoPackage was designed and developed to support the storage of styling data. The development of styling extension involves creation of data tables that is styling data model into the existing GeoPackage data model. The main function of the styling data model is to store styling records for geographic data layers within the GeoPackage. The capabilities of the new data model were tested in cross-platform applications including Windows, Linux, and Mac operating system. The testing was limited to vector data types such as point, line, and polygon, which represent geographic data layers. Results show that GeoPackage with the built-in styling extension is capable to store styling data, which can be loaded to cross-platform applications without the need for format conversion. In addition, the extension stores styling records together with the geographical data layers in a single file format (i.e. *.gpkg), in contrast to the use of other stylesheets, which store styling records in separate file format. This is possible because GeoPackage is a cross-platform geospatial data format that supports interoperability and thus, only requires single file format. Finally, this study successfully explores the capability of GeoPackage data format in maintaining and storing cartographic styling.